Recurrent adnexal lymphoma in a horse. (27th October 2017) - Martabano, B. B.; Brooks, D. E.; Whitley, R. D.; Proietto, L. R.; Conway, J. A.; Zoll, W. M.; Plummer, C. E.
Summary: Lymphoma is a relatively uncommon neoplasm in the horse; however, it is considered the most common neoplasia of the equine haemolymphatic system. Limited reports of adnexal lymphoma have been documented in the literature, with no known reports of recurrence nearly a decade after mass excision. The objective is to describe a case of recurrent adnexal lymphoma in a 20‐year‐old Quarter Horse gelding presented to the Ophthalmology service at the University of Florida Veterinary Hospital (UFVH) for evaluation of a solitary subconjunctival mass of the right eye (OD). A focal, pink, fleshy mass associated with the dorsomedial bulbar conjunctiva was noted. An excisional biopsy was performed. Histopathology revealed lymphoma with clean margins. The client declined staging and further therapy at the initial visit. Approximately 8 years later, the horse began to exhibit intermittent mild to moderate diffuse swelling of the conjunctiva OD. Six months after onset, the swelling worsened acutely and was accompanied by severe swelling of the left conjunctiva (OS). The horse then returned to UFVH and was diagnosed with diffuse, bilateral conjunctival lymphoma. Humane euthanasia was elected. T cell lymphoma was confirmed with immunohistochemistry performed post‐mortem. At necropsy, neoplastic tissue was observed throughout the adnexal and ocular tissues of both eyes and in the submandibular lymph nodes. Adnexal lymphoma is an uncommon neoplasm in the horse. To the authors' knowledge, this is the first documentation of a nodular adnexal lymphoma that involved an 8‐year period without recurrence followed by development of diffuse, bilateral disease. Typically, surgical excision of the nodular form of lymphoma involving the extraocular tissues yields an improved prognosis compared with the diffuse form of the disease. Further investigation is necessary to determine if nodular forms of adnexal lymphoma represent early stages of diffuse extraocular or systemic disease.